ETHNOLECT AND MULTIETHNOLECT: NEW FORMS OF LANGUAGE CHANGE IN GERMAN (TAMADDUN NURI JURNALI, 2025)
This article analyses the sociolinguistic aspects of the concepts of ethnolect, sociolect and multiethnolect and their impact on social identification processes in German. Furthermore, the article examines the communicative and identificational role of the ethnolects and multiethnolects that have emerged in German on the basis of empirical examples.